Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Royal English Malang - Ihwanul Mutaqin; Abd Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to determine the effect of the work environment and work motivations on employee performance at Royal English Malang. The population of this study were all Royal English Malang employees, amounting to 32 employees. Data analysis method used in this research is quantitative analysis method.Researchers in this case used questionnaire media and primary data. The questionnaire used in this study is a direct and closed questionnaire, where the questionnaire is directly given to respondents and respondents can choose one of the alternative answers that are available. Based on the results of the study it can be seen that the work environment and work motivation significantly influence employee performance at Royal English Malang.Keywords: Work environment, Work Motivation, Performance